KEPADATAN POPULASI LUTUNG JAWA (Trcyphitecus auratus) DI TAMAN WISATA ALAM PANGANDARAN - Ryan Wahyu (Fakultas Kehutanan Universitas Winaya Mukti, 2021)
Pangandaran Nature Park is a tourist forest area as well as a conservation area and become one of Javan Langur, but the data is still very limited. This study aims to find out the number of individuals and groups of javan langur who are in the nature park pangandaran. This study was conducted in November 2020. Javan langur population is calculated using path and concentration count methods. The data collected are number of individuals, number of groups, gender and age structure (Infants, Children, Adolescents, and Adults). Observations were made as many as 36 times with 3 observations on one day namely morning (06.00 AM), noon (11:00 AM), and evening (15:00 PM). The result showed that there were 64 javan langur individuals divided into 4 groups with an alleged population density of 2.60 individuals/hectare. The ratio of male and female javan langur in pangandaran nature park is 1:2 where the female javan langur is more than the male. And for structure of most javan langur age in the adolescents age class with a percentage of 51.6 %, then adults 28.1%, children 12.5%, and the lowest there is in the infant class with a percentage of 7.8%.